Network Design and Activation Fiber to The Building (FTTB) and Measurement of The Damage Value of Optical Distribution Frame (ODF) To Optical Distribution Cabinet (ODC) - Safitri, Eka; Asril, Aprinal Adila; Vitria, Rikki (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
The need for high-speed internet continues to increase with technological developments. Fiber to the Building (FTTB) is a solution for providing fast internet access to commercial and residential buildings. However, the main challenge in maintaining network quality is attenuation in fiber optic cables, especially at connections. This research aims to analyze the effect of pigtail cable length and connection quality on the total attenuation from the Optical Distribution Frame (ODF) to the Optical Distribution Cabinet (ODC) in the FTTB network, both before and after activation. The research method uses pigtail cables of varying lengths, from 30 cm to 150 cm. Some connections are carried out according to Standard Operating Procedures (SOP), while others are not, to measure the effect of connection quality on attenuation. Measurements were carried out using an Optical Power Meter (OPM) and Passive Optical Network (PON) technology with an SFP of 8 dB. The research results show that connections that comply with the SOP produce lower attenuation, namely 7.16 dB on a 150 cm cable, 7.09 dB on a 120 cm cable, and 6.99 dB on a 100 cm cable. On the other hand, connections that do not comply with the SOP produce higher attenuation, namely 8.15 dB on an 80 cm cable, 8.08 dB on a 50 cm cable, and 8.02 dB on a 30 cm cable. This research contributes to the optimization of FTTB network installations.